OIL CONTENT OF THE SEEDS OF PRUNUS PERSICA var. NECTARINA (Scientific journal of the Fergana State University, 2025)
The oil content, fatty acids, neutral lipids, glycolipids, and phospholipids composition of the seeds of Prunus persica var. nectarina growing in Uzbekistan has been determined and analyzed. The neutral lipid (NL), glycolipid (GL), and phospholipid (FL) fractions of the oil extracted from two different types of nectarines were isolated. The three obtained fractions were hydrolyzed, and the fatty acids were converted into methyl esters for analysis using chromatographic mass spectrometry. The amount of saturated fatty acids in the neutral lipids was found to be 8.45-8.87%, while the amount of unsaturated fatty acids was 91.13-91.55%. According to the analysis results, 15 saturated and unsaturated fatty acids were identified in the studied nectarine samples. The amounts of oleic and linolenic acids were found to be 68.84-69.05% and 21.71-21.98%, respectively. Among the saturated fatty acids, palmitic acid was present in the highest quantity. Nectarine oil is recommended for the preparation of enriched vegetable oils and various food supplements.